KROTIC: Kit de Robótica Costarricense Versión Extendida - Villegas-Lemus, Milton (Instituto Tecnológico de Costa Rica., 2017)
Krotic Costa Rican Robotic Kit is an outcome of a VIE research project during 2008-2010. The robotic kit was constructed for educational purposes with a cost of $75. The structural analysis was continued thanks to the support of the CIC and de Computer Science School, achieving a very nice, attractive and functional design allowing the robot be used in different kind of learning projects. The main goals of Extended Version of Krotic project are: construct a programmer device for the robot without using regular computer; a camera module; a wireless communication module; program and evaluation of a Subsumption architecture measuring energy consumption; propose a didactical plan to use in 3 elementary schools as a pilot test. During the design and construction process development kits and circuits available were assessed. Some variable were measured specially consumption, which is a state variable in these systems. Once the circuits were finished, ten robotic kits were constructed in order to use them with the programmer in a pilot plan in the schools. Two programming modules were constructed. The time response for every algorithm in the different device constructed were measured. The project achieved all the objectives set, the main conclusion states that it is better have a dedicated microcontroller for the execution of the Subsumption subroutines and for the rest of the robot jobs have another microcontroller.
IProyecto de Investigación Instituto Tecnológico de Costa Rica. Vicerrectoría de Investigación y Extensión (VIE). Escuela de Ingeniería en Computación. Centro de Investigaciones en Computación (CIC), 2017
Keywords: Educación; Arquitectura; Robots; Aprendizaje; Sistemas; Research Subject Categories::TECHNOLOGY::Information technology